The Effect Of Using Elsa Speak Application To Improve Students’ Pronunciation - Sonia Febri, Yesi (Jolly Journal of English Education, 2023)
Based on researcher observation, it was found some of the students have problem when pronouncing several words. This research discusses The Effect of Using Elsa Speak Application to Improve Student’s Pronunciation. The purpose of this research was to find how the effect of ELSA Speak Application to improve students’ pronunciation. The design of this research was pre-experimental with quantitative approach. The researcher used cluster sampling that choose 1 class that consisted 19 students. Technique of collecting data is using pronunciation test. the researcher gave pre-test before give the treatment by using ELSA Speak Application, and give the posttest after treatment. The technique of data collecting was a test. The technique of data analyzing data, the researcher used paired sample t-test formula by using SPSS 22. After analyzing the data, the researcher found that there is a significant effect of using ELSA Speak Application to improve students’ pronunciation.